The Effect Of Supplementary Food Supply (PMT) Supervision Local For Pregnant Women With Chronic Energy Deficiency (CED) On The Nutritional Status Of The Mother - Ulfia Fitrianingsih; Yesi Putri; Indah Eriska; Zella Choirun Ni`mah (International Journal of Health Engineering and Technology, 2026)
Chronic energy deficiency (CED) in pregnant women is a major public health challenge. Globally, the WHO reports that approximately 38 million pregnant women experience malnutrition each year, including CED, which contributes to an increased risk of maternal and neonatal mortality. In Indonesia, based on 2018 Riskesdas data, the prevalence of CED in pregnant women reached 17.3% (Ministry of Health of the Republic of Indonesia, 2023b). CED in pregnant women, identified by an upper arm circumference (LILA) of less than 23.5 cm, has serious impacts on maternal and fetal health, such as increasing the risk of low birth weight (LBW), premature birth, hypothyroidism, and stunting (Supadmi et al., 2020). This problem poses a major challenge in efforts to reduce maternal and infant mortality and improve the quality of public health. This study aims to determine the effect of local supplementary feeding (PMT) assistance for pregnant women with chronic energy deficiency (CED) on maternal nutritional status. This research was conducted in May 2026. This type of research is quantitative research using a Pre-Experimental design with a one group pretest posttest design approach . The sampling technique was carried out using a purposive sampling method . The sample used in this study was 18 respondents. The instruments used were questionnaires and PMT assistance sheets. The average nutritional intake before assistance was 42.3 calories and after assistance was 73.4 calories, while the LiLA measurement before assistance was 22.3cm and after assistance was 23.3cm. There is an effect of local supplementary feeding assistance (PMT) for pregnant women with chronic energy deficiency (KEK) in the work area of the Sindang Danau Health Center UPT on maternal nutritional status, with an increase in nutritional intake between 20.9 calories to 38.6 calories and an increase in LiLA size between 0.5 cm to 1.6 cm.